Gut microbiota interplay with autophagy-EMT dynamics in colorectal cancer - Vescovo, Tiziana; Bontempi, Giulio; Bayat, Mohammadreza; Piredda, Lucia; Fidaleo, Marco; Strippoli, Raffaele; Antonioli, Manuela (Frontiers in Cell and Developmental Biology, 2025)
The human microbiota is composed of a complex community of microorganisms essential for maintaining host homeostasis, especially in the gastrointestinal tract. Emerging evidence suggests that dysbiosis is linked to various cancers, including colorectal cancer (CRC). The microbiota contributes to CRC development and progression by influencing inflammation, genotoxic stress, and key cell growth, proliferation, and differentiation pathways. Certain bacterial species, including Fusobacterium nucleatum and Escherichia coli, play a role in tumorigenesis by facilitating epithelial-mesenchymal transition (EMT), perturbing autophagy, and supporting immune evasion. In contrast, beneficial microorganisms such as Bifidobacterium and Lactobacillus provide protective effects by boosting immune surveillance and supporting the integrity of the intestinal barrier. This review examines the complex connection between gut microbiota and CRC, emphasizing how changes in microbial composition facilitate tumor development and influence treatment outcomes. We cover recent progress in microbiota-based biomarkers for CRC diagnosis and prognosis, showcasing their promise for early detection and improved patient stratification. Furthermore, we explore microbiota-focused therapeutic methods such as probiotics, prebiotics, faecal microbiota transplantation (FMT), and precision antibiotics, which show potential to complement standard CRC treatments. By highlighting the latest advancements in this area, we emphasise how microbiome research is transforming our comprehension of CRC and leading to new diagnostic and treatment approaches.